Time limit for submitting application to determine a medical incident: analysis and comments de lege ferenda (Ius Novum, 2020)
The aim of this article is to critically assess the time limit for submitting an application for determining a medical incident. The starting point for the evaluation of Article 67c paras 2 and 4 of the Act on patients’ rights and Patient Ombudsman is the inference that this time limit should be qualified as final. This conclusion in particular impacts the effects of its expiry and the lack of possibility – contrary to the individual rules of procedure of voivodship committees deciding on medical incidents in which the time limit is defined under procedural law – for its restoration. The analysis of the solution adopted by the legislator is also conducted through the prism of its comparison with the statutory period of limitation in claims for compensation for damage caused by a wrongful act (Article 4421 § 3 Civil Code). This comparison leads to the conclusion that the time limit for submitting an application for determining a medical incident significantly limits access to this alternative method of redressing damage caused by medical treatment.
Keywords: medical incident; application for determining a medical incident; substantive-law final time limit; compensation for damage